High-temperature-resistant silicon-aluminum molecular sieve-based aerogel and preparation method thereof
By using silicon-aluminum molecular sieve as a basis and combining solization and gelation processes, high-thermal stability and low-density silicon-aluminum molecular sieve-based aerogels are prepared, which solves the problem of easy sintering of SiO2 aerogels in high temperature environments, and realizes the preparation of lightweight, high-temperature-resistant heat-resistant anti-insulating materials.
Patent Information
- Application Number
- CN202411829918.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
The existing SiO2 aerogels are prone to sintering and collapse in high temperature environments, resulting in a reduced thermal insulation effect and it is difficult to adapt to the application needs of long-term high-temperature environments.
Silicon-aluminum molecular sieve is used as the matrix to prepare a silicon-aluminum molecular sieve-based aerogel with high thermal stability and low density through solization, dispersion and gelation processes. The process includes stirring the silicon-aluminum molecular precursor with the catalyst solution, washing and centrifuging after crystallization reaction, followed by acid activation treatment, adding a binder and a base catalyst for gel reaction and aging treatment, and finally obtaining a silicon-aluminum molecular sieve-based aerogel through drying.
It significantly improves the high-temperature resistance and thermal stability of the material, reduces density, and obtains a lightweight, high-temperature-resistant silicon-aluminum-based aerogel heat-proof insulation material, suitable for high-temperature environments.
Smart Images

Figure CN119657000A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of silicon compounds, and in particular relates to a high temperature resistant silicon-aluminum molecular sieve-based aerogel and a preparation method thereof. Background Art
[0002] SiO2 aerogel is the most mature aerogel system studied. It is composed of small-sized particles in the shape of pearl chains, with a slender three-dimensional skeleton and high surface energy. Generally speaking, traditional SiO2 aerogel has good thermal insulation performance in medium and low temperature applications below 600°C, but in long-term high temperature environments exceeding 600°C, the internal structure is prone to sintering and collapse, and the material will shrink significantly on a macro scale, greatly reducing the heat insulation effect, thus limiting its application in high temperature environments. Through process optimization, doping, compounding and other means, the temperature resistance of SiO2 aerogel can be improved, so that it can better adapt to high temperature environments, further expand its scope of application, and meet the needs of more fields.
[0003] Existing studies have shown that doping aluminum in silica aerogel to form Si-O-Al bonds can help improve thermal stability. In particular, a local electronegative Si-O-Al structure is formed on the surface of the particles. The electrostatic repulsion generated can inhibit the sintering of silica nanoparticles at high temperatures, thereby improving high-temperature stability (Ceram. Int., 2022 (48): 15006-15016). Patent CN115108809A uses orthosilicate and inorganic aluminum source as co-precursors, acid-base catalysis and synchronous hydrolysis in the liquid phase to prepare aluminum-doped alumina sol, introduces inorganic ceramic fiber preforms by vacuum pressure impregnation, and then obtains a modified silica aerogel thermal insulation composite material with a maximum operating temperature of 1100°C after supercritical drying with ethanol.
[0004] Aluminum silicate materials have higher temperature resistance than conventional silica aerogels. Aluminum silicate fiber is a lightweight, energy-saving, fireproof ceramic fiber with the advantage of low thermal conductivity [≤0.128W / (m·K)]. It can be used in environments above 1000°C and can still maintain good performance when the temperature reaches 1300°C (Tang Jie, et al. Fine Chemicals, 2024, 13:61-63). However, for thermal insulation materials, the thermal conductivity is relatively high and it is difficult to achieve a good thermal insulation effect. Another molecular sieve material with regular arrangement of silicon and aluminum atoms can achieve a temperature resistance of more than 1000°C by adjusting the silicon-aluminum ratio and pore structure. The morphology of molecular sieve crystals is varied, including cubic, rod-shaped, and flat-plate shapes, and the scale can be adjusted between nanometer and micrometer levels. The pores of the molecular sieve are built from primary structural units composed of atoms and are part of the crystal structure. Therefore, the skeleton is resistant to high temperatures and has better mechanical strength, which overcomes the shortcomings of poor mechanical strength of aerogels. In addition, as a porous material, molecular sieve material has a large specific surface area, high porosity, and "infinite" pore distribution, which can greatly reduce the heat transfer between solids and hinder the heat convection generated by the flow of gas molecules. The porous structure on the surface can reflect and scatter part of the infrared thermal radiation (Dong Xue, master's thesis, Jilin University, 2013).
[0005] Zhang Tao (PhD thesis, Jilin University, 2014) used microporous (<2nm) ZSM-5 molecular sieves and mesoporous (2-50nm) SBA-15, MCM-41, and MAS-5 molecular sieves with a small amount of microporous structure to prepare a zeolite with a density of 0.6-0.75g / cm 3 The thermal insulation sheet has a thermal conductivity of 0.017-0.04W / (m·K) based on the international ASTM C518091 thermal conductivity test standard, and has good thermal insulation performance. The pore size of these molecular sieves is lower than the average free path of air molecules (70nm), which helps to inhibit the convective heat transfer of gases.
[0006] The high-performance silicon-aluminum heat-insulating materials prepared by the prior art have the following main disadvantages:
[0007] (1) The preparation of silica-alumina aerogels is difficult, and the process controllability is poor. For example, in the single-molecule precursor co-hydrolysis method, the hydrolysis rate of aluminum salt is fast, which is difficult to match the sol-gel time window of the silica precursor, and a chelating agent and fine parameter adjustment are required; in the silica sol and aluminum sol co-gel method, aluminum sol is difficult to exist stably in the pH range of 4-9, which affects the control of the co-gel time window, and the preparation time is long and the process is complicated.
[0008] (2) Silica-alumina molecular sieve material has high temperature resistance and low thermal conductivity, and is a good thermal insulation material. However, when it is prepared as an integrated solid insulation material, its density is high, which is not conducive to the development of lightweight thermal insulation materials. Summary of the invention
[0009] The purpose of the present invention is to provide a high-temperature resistant silica-alumina aerogel and a preparation method thereof. By adopting silica-alumina molecular sieve as a base element and combining processes such as sol formation, dispersion, and gelation, the thermal stability and porosity of the material are improved and the density is reduced, and finally a lightweight, high-temperature resistant silica-alumina based aerogel heat-insulating material is obtained.
[0010] The technical solution adopted by the present invention to achieve its purpose is as follows:
[0011] A method for preparing a high temperature resistant silicon-alumina molecular sieve-based aerogel comprises the following steps:
[0012] (1) adding a silicon-aluminum molecular precursor to a catalyst solution and stirring to obtain a mixed sol, and after a crystallization reaction, washing and centrifuging to obtain microporous or mesoporous silicon-aluminum molecular sieve nanocrystals;
[0013] (2) using an acid to pre-activate the molecular sieve nanocrystals to increase the content of silanol and aluminum hydroxyl groups on their surfaces, thereby obtaining an activated silicon-aluminum molecular sieve sol;
[0014] (3) Adding a binder and an alkali catalyst to the activated silica-alumina molecular sieve sol, performing a gel reaction and an aging treatment, and then drying to obtain a silica-alumina molecular sieve-based aerogel.
[0015] Furthermore, in step (1), the silicon-aluminum molecular precursor includes an aluminum source and a silicon source, and the solid content of the silicon-aluminum molecular sieve sol is 12%-35%, and the amount of the silicon-aluminum molecular precursor added is determined according to the solid content.
[0016] Furthermore, in step (1), the aluminum source is aluminum isopropoxide, the silicon source is tetraethyl orthosilicate or silica sol, and the catalyst solution is tetraethylammonium hydroxide solution; if the silicon source is silica sol, a phosphoric acid solution is also added.
[0017] Furthermore, the crystallization reaction conditions in step (1) are crystallization at 150-170° C. for 18-24 hours.
[0018] Furthermore, the molecular sieve type of the silicon-aluminum molecular sieve nanocrystals in step (1) is one of ZSM-5, SAPO-34, SSZ-39, type A, type X or type Y; and the morphology of the molecular sieve is a one-dimensional nanocrystalline or two-dimensional nanosheet molecular sieve.
[0019] Furthermore, in step (2), the acid is one or more of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, acetic acid, and citric acid. After the acid is added, the pH of the solution is between 1 and 3. The pretreatment time is 0.5 to 24 hours, and the pretreatment temperature is room temperature to 60°C.
[0020] Furthermore, in step (2), a dispersant is added during the acid pretreatment process, and the dispersant is one or more of chitosan, hydroxypropyl methylcellulose, and polyacrylamide, and the amount of the dispersant is 1% to 5% of the total solution mass.
[0021] Furthermore, in step (3), the adhesive is selected from one of silane coupling agent, methyl orthosilicate, ethyl orthosilicate, silica sol, and aluminum borosilicate sol, and the amount of the adhesive is 5% to 25% of the total mass of the solution.
[0022] Furthermore, in step (3), the alkaline catalyst is one or more of ammonia water, tetramethylammonium hydroxide, tetraethylammonium hydroxide, and ethylenediamine, and after the alkaline catalyst is added, the pH value of the solution is adjusted to 6 to 9.
[0023] Furthermore, the temperature of the gel reaction in step (3) is room temperature to 100° C., preferably 40 to 60° C.; the aging conditions are 60 to 250° C., 24 to 96 h, preferably 80 to 120° C., 48 to 96 h.
[0024] Furthermore, in step (3), the drying method is atmospheric pressure drying, supercritical drying or freeze drying; wherein, after aging, the product is replaced by ethanol and then subjected to supercritical drying or freeze drying; and when the product is dried at atmospheric pressure, methyltrimethoxysilane or hexamethyldisiloxane is used for hydrophobic treatment after ethanol replacement.
[0025] A high temperature resistant silicon-alumina molecular sieve-based aerogel is prepared by the above preparation method.
[0026] Beneficial effects achieved by the present invention:
[0027] (1) The present invention adopts silicon aluminum molecular sieve as the basic element, which effectively improves the high temperature resistance and thermal stability of the material.
[0028] (2) The present invention successfully prepares aerogels with a macroscopic three-dimensional structure by subjecting the silica-alumina molecular sieve to sol-forming and dispersion treatment and then to a gel process, thereby significantly increasing the porosity and reducing the density.
[0029] (3) The silica-alumina molecular sieve-based aerogel material prepared by the present invention is lightweight, high temperature resistant, has good heat insulation performance, and is suitable for use in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of preparing high temperature resistant silicon aluminum molecular sieve based aerogel. DETAILED DESCRIPTION
[0031] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below in conjunction with embodiments.
[0032] Embodiment 1:
[0033] (1) Aluminum isopropoxide is added to an aqueous solution of tetraethylammonium hydroxide (TPAOH), and the mixture is stirred at 0°C to obtain a clear solution. Tetraethyl orthosilicate (TEOS) is added and stirred at room temperature for 2 hours until TEOS is completely dissolved. The materials in the mixed sol are 1Al2O3:60SiO2:20TPAOH:650H2O. The mixture is crystallized at 150°C for 24 hours. After washing and high-speed centrifugation, ZSM-5 nanocrystals are obtained.
[0034] (2) 60 mL of an acid solution with a pH of 1.5 was prepared using 1 mol / L H2SO4, 15 g of the prepared ZSM-5 molecular sieve nanocrystals and 2 g of chitosan were added, and the mixture was stirred for 4 h.
[0035] (3) Add 10 g of silane coupling agent KH550, stir for half an hour, adjust the pH to 6 with ammonia water, transfer the solution into a hydrothermal autoclave, perform gelation at 60°C and age at 80°C for 48 hours. The solid gel obtained by aging is solvent-displaced in ethanol three times, and then supercritically dried. After drying, methyltrimethoxysilane is used for hydrophobic treatment to obtain a silica-alumina molecular sieve-based aerogel that can be stored for a long time.
[0036] The above-mentioned silica-alumina molecular sieve-based aerogel was heat-treated at 900°C, and its shrinkage was measured to be 0.8%. The specific surface area distribution before and after calcination was 562.5 m 2 / g and 534.8m 2 / g, the thermal conductivity before and after the test is 0.020W / m / k and 0.021W / m / k.
[0037] Embodiment 2:
[0038] (1) Aluminum isopropoxide was dissolved in tetraethylammonium hydroxide solution, stirred for 3 h, silica sol was added and stirred for another 2 h, phosphoric acid solution was slowly added dropwise, and the materials in the mixed sol were 1Al2O3:2P2O5:4TPAOH:0.6SiO2:120H2O. The mixture was crystallized at 170°C for 18 h, washed and centrifuged at high speed to obtain SPAO-34 flaky nanocrystals.
[0039] (2) 30 mL of an acid solution with a pH of 2 was prepared using HNO 3 , 8 g of the prepared SAPO-34 molecular sieve nanocrystals and 1.2 g of hydroxypropyl methylcellulose were added, and the mixture was stirred for 5 h.
[0040] (3) Add 2 g of methyl orthosilicate, stir for 1 hour, adjust the pH to 6.5 with tetraethylammonium hydroxide solution, transfer the solution into a hydrothermal autoclave, perform gelation at 40° C. and age at 90° C. for 96 hours. The solid gel obtained by aging is solvent-displaced in ethanol for 3 times, and then supercritically dried. After drying, hexamethyldisiloxane is used for hydrophobic treatment to obtain a silica-alumina molecular sieve-based aerogel that can be stored for a long time.
[0041] The silica-alumina molecular sieve-based aerogel was heat-treated at 800°C, and its shrinkage was measured to be 0.2%. The specific surface area distribution before and after calcination was 353.4 m 2 / g and 342.4m 2 / g, the thermal conductivity before and after the test is 0.023W / m / k and 0.023W / m / k.
[0042] Embodiment 3:
[0043] (1) Aluminum isopropoxide was dissolved in tetraethylammonium hydroxide solution, stirred for 3 h, silica sol was added and stirred for another 2 h, phosphoric acid solution was slowly added dropwise, and the materials in the mixed sol were 1Al2O3:2P2O5:4TPAOH:0.6SiO2:120H2O. The mixture was crystallized at 170°C for 18 h, washed and centrifuged at high speed to obtain SPAO-34 flaky nanocrystals.
[0044] (2) 30 mL of an acid solution with a pH of 1.5 was prepared using HNO3, 9 g of the prepared SAPO-34 molecular sieve nanocrystals and 1.2 g of chitosan were added, and the mixture was stirred for 6 h.
[0045] (3) 1.6 g of ethyl orthosilicate was added, stirred for 1 hour, and the pH was adjusted to 8 with aqueous ammonia. The solution was transferred to a hydrothermal autoclave, and gelled at 40° C. and aged at 120° C. for 96 hours. The solid gel obtained by aging was solvent-displaced in ethanol for 3 times, and then supercritically dried. After drying, hexamethyldisiloxane was used for hydrophobic treatment to obtain a silica-alumina molecular sieve-based aerogel that can be stored for a long time.
[0046] The silica-alumina molecular sieve-based aerogel was heat-treated at 1000°C, and its shrinkage was measured to be 1.5%. The specific surface area distribution before and after calcination was 336.7 m 2 / g and 305.5m 2 / g, the thermal conductivity before and after the test is 0.026W / m / k and 0.027W / m / k.
[0047] Comparative Example 1:
[0048] Take 100g of deionized water, add ethyl orthosilicate according to 25% SiO2 solid content (the proportion of total mass of water + silicon precursor), add 2g of 1mol / L HNO3 solution, stir and hydrolyze for 1h, then add 1.8g of 1mol / L ammonia water, stir and mix thoroughly. After gelation, age at 90℃ for 3 days, replace the aged wet gel with ethanol 3 times within 2 days to obtain alcohol gel, and perform supercritical drying. Use hexamethyldisiloxane for gas phase hydrophobicity to obtain SiO2 aerogel that can be stored for a long time.
[0049] The SiO2 aerogel was heat treated at 800℃ and its shrinkage was measured to be 24%. The specific surface area distribution before and after calcination was 598.5m 2 / g and 73.6m 2 / g, the thermal conductivity before and after the test is 0.021W / m / k and 0.055W / m / k.
[0050] Comparative Example 2:
[0051] Take 100g of deionized water, add 2.5g of hexadecyltrimethylammonium chloride and 0.2g of acetic acid, add methyltrimethoxysilane according to 20% of SiO2 solid content, stir vigorously for hydrolysis for 2h, add 0.5g of 1mol / L NH3·H2O solution, stir for 20min, let gel stand, and age at 120℃ for 3 days. The aged gel is directly dried at normal pressure for 3 days, then gradient dried at 60℃ and 150℃ for 8h, and gas-phase hydrophobicized with hexamethyldisiloxane to obtain high-temperature resistant SiO2 aerogel that can be stored for a long time.
[0052] The SiO2 aerogel was heat treated at 800℃ and its shrinkage was measured to be 22%. The specific surface area distribution before and after calcination was 312.4m 2 / g and 63.2m 2 / g, the thermal conductivity before and after the test is 0.028W / m / k and 0.057W / m / k.
[0053] The performance of the aerogels prepared in the above examples and comparative examples was tested, and the test results are shown in Table 1.
[0054] Table 1 Summary of test data of embodiments and comparative examples
[0055]
[0056] By comparing the test data in Table 1, it can be seen that by using silica-alumina molecular sieve nanocrystals as raw materials and obtaining silica-alumina molecular sieve-based aerogel materials with high thermal stability through sol-gel reaction, the shrinkage rate is greatly controlled (within 2%) after high-temperature treatment, and the specific surface area is well retained, indicating that the pore structure is supported and protected, and the aerogel structure is maintained at high temperatures, which helps to effectively inhibit high-temperature gas-phase heat transfer and play a high-temperature heat-insulating role.
[0057] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.
Claims
1. A method for preparing a high temperature resistant silicon-alumina molecular sieve-based aerogel, characterized in that: The following steps are involved: (1) adding a silicon-aluminum molecular precursor to a catalyst solution and stirring to obtain a mixed sol, and after a crystallization reaction, washing and centrifuging to obtain microporous or mesoporous silicon-aluminum molecular sieve nanocrystals; (2) using an acid to pre-activate the molecular sieve nanocrystals to increase the content of silanol and aluminum hydroxyl groups on their surfaces, thereby obtaining an activated silicon-aluminum molecular sieve sol; (3) Adding a binder and an alkali catalyst to the activated silica-alumina molecular sieve sol, performing a gel reaction and an aging treatment, and then drying to obtain a silica-alumina molecular sieve-based aerogel.
2. The preparation method according to claim 1, characterized in that In step (1), the silicon-aluminum molecular precursor includes an aluminum source and a silicon source, and the solid content of the silicon-aluminum molecular sieve sol is 12%-35%; the aluminum source is aluminum isopropoxide, the silicon source is tetraethyl orthosilicate or silica sol, and the catalyst solution is tetraethylammonium hydroxide solution; if the silicon source is silica sol, a phosphoric acid solution is also added.
3. The preparation method according to claim 1, characterized in that: The crystallization reaction conditions in step (1) are crystallization at 150-170° C. for 18-24 hours.
4. The preparation method according to claim 1, characterized in that: The molecular sieve type of the silicon aluminum molecular sieve nanocrystals in step (1) is one of ZSM-5, SAPO-34, SSZ-39, type A, type X or type Y; the morphology of the molecular sieve is a one-dimensional nanocrystalline or two-dimensional nanosheet molecular sieve.
5. The preparation method according to claim 1, characterized in that: In step (2), the acid is one or more of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, acetic acid, and citric acid. After the acid is added, the pH value of the solution is between 1 and 3. The pretreatment time is 0.5 to 24 hours, and the pretreatment temperature is room temperature to 60° C. A dispersant is also added during the acid pretreatment process. The dispersant is one or more of chitosan, hydroxypropyl methylcellulose, and polyacrylamide, and the amount of the dispersant is 1% to 5% of the total solution mass.
6. The preparation method according to claim 1, characterized in that: In step (3), the adhesive is selected from one of silane coupling agent, methyl orthosilicate, ethyl orthosilicate, silica sol, and aluminum borosilicate sol, and the amount of the adhesive is 5% to 25% of the total mass of the solution.
7. The preparation method according to claim 1, characterized in that: In step (3), the alkaline catalyst is one or more of ammonia water, tetramethylammonium hydroxide, tetraethylammonium hydroxide, and ethylenediamine. After the alkaline catalyst is added, the pH value of the solution is adjusted to 6 to 9.
8. The preparation method according to claim 1, characterized in that: The temperature of the gel reaction in step (3) is room temperature to 100° C.; the aging conditions are 60 to 250° C. for 24 to 96 hours.
9. The preparation method according to claim 1, characterized in that: The drying method in step (3) is atmospheric pressure drying, supercritical drying or freeze drying; wherein, after aging, the mixture is replaced by ethanol and then supercritical drying or freeze drying is performed; and when drying under atmospheric pressure, methyltrimethoxysilane or hexamethyldisiloxane is used for hydrophobic treatment after ethanol replacement.
10. A high temperature resistant silicon aluminum molecular sieve based aerogel, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high-temperature-resistant modified silicon oxide aerogel heat-insulation composite material
CN115108809A